The Effect of Teledentistry Counseling on Improving Dental Health Knowledge and Toothbrushing Habits Among the Elderly: Teledentistry and Oral Health Knowledge in the Elderly - Mutiara Khasanah; Yuly Peristiowati; Agustin Widyowati (Innovative Approaches in Health Science Journal, 2026)
Background: The elderly are a vulnerable group to dental health problems due to physiological changes, poor toothbrushing habits, and limited access to dental health services. These conditions pose a serious challenge in maintaining their quality of life. Teledentistry has emerged as an innovative solution to provide remote dental health counseling and education. This study aimed to analyze the effect of teledentistry counseling on improving dental health knowledge and toothbrushing habits among the elderly in Benda District, Tangerang City. Methods: This study employed a quantitative design with a quasi-experimental two-group pretest–posttest approach. The sample consisted of 100 elderly participants divided into an intervention group (teledentistry counseling) and a control group (leaflet). Data were collected using a structured questionnaire assessing dental health knowledge and toothbrushing habits. Data analysis included validity and reliability tests, normality testing, Wilcoxon Signed Rank Test, paired t-test, and independent t-test. Results: The results showed a significant increase in dental health knowledge and toothbrushing habits among the elderly after receiving teledentistry counseling (p < 0.05). The average post-test score of the intervention group was higher than that of the control group, which received only leaflets without interactive counseling. Conclusion: Teledentistry-based counseling was proven effective in improving dental health knowledge and toothbrushing habits among the elderly. This strategy can serve as a practical solution to enhance the quality of dental health services, particularly in areas with limited access to health facilities.